Grace under fire - Garwood, Julie (Berkley, 2022)
"A Navy SEAL will need every bit of his extensive skill set when he appoints himself as bodyguard to a woman determined not to need one in this thrilling new novel from #1 New York Times bestselling author Julie Garwood. Isabel Grace MacKenna had a hundred things to do today. Killing someone wasn't one of them. It was supposed to just be a quick visit to Boston for the Buchanans' anniversary party. But after getting lost, she ends up with a wounded man stumbling into her and then his shooter coming after them both. When she fires back in self-defense, she doesn't expect him to drop dead. The police are torn between believing that she's an innocent bystander or more deeply involved, but thanks to the Buchanans dispatching Navy SEAL and now lawyer Michael Buchanan to deal with the police, Isabel is finally free to go. Isabel knows that she should be more grateful for Michael's help, but since she loathed him for years, gratitude is the last thing she feels. But somehow, Michael has appointed himself her de facto guardian, and he's sticking to her like glue despite their constant bickering and sizzling attraction. Even when Isabel goes to Scotland to claim her inheritance, Michael follows her, but he isn't the only thing Isabel can't shake. Mysterious threats against Isabel have escalated, and before they can deal with their growing feelings for each other, they must first survive"--